Advancements in Helicobacter pylori: A Novel Culture AA-Medium for Helicobacter pylori Detection - AlRubaye, AbdulRahman; Al-Thwaini, Amina N. (Technium BioChemMed, 2024)
This research provides crucial insights into the detection and culturing of Helicobacter pylori, a significant pathogen associated with gastric diseases. New culture media were prepared as X1, X2 and X3 in comparison with Columbia blood agar. Culturing success varied between Columbia blood agar and the novel X1-media which named as AA-media, while it failed on X2-media and X3-media. 48.8% of the positive samples were successfully cultured on Columbia blood agar and AA-media. Remarkably, colonies on AA-media displayed larger and distinct features within the first 24 hours, a stage achieved on Columbia blood agar after 48 hours. This research underscores the importance of considering alternative culture media to improve culture processing and obtaining rapid and distinctive results for the accurate diagnosis of Helicobacter pylori-associated diseases.